Sistema de logística inversa para la generación de beneficio económico en empresas del sector eléctrico - Salas Sarayasi, Luis Alberto (2023)
The aim of this research is to propose a reverse logistics system that enhances the unbundling process of goods meant for disposal, from the generation phase to final disposal, specifically designed for companies in the electric transmission sector in Peru, which can be replicated in power generation and distribution companies. Such improvements are expected to have a positive impact on all areas involved in the process, streamlining activities while applying current technological tools. Upon conducting a cost-benefit analysis and implementing the new process and its support tools, the expected outcome is an 87% increase in economic benefits compared to the current empirical process, supported by a self-developed technological tool, specific service agreement levels, and real-time information management. This non-experimental applied research employs both quantitative and qualitative methodologies and techniques such as observation, interviews, data collection, and data analysis. To develop this study, an initial diagnosis was conducted, followed by the definition of objectives, identification of relevant aspects, and development of a proposal under the premise of continuous improvement.